Pd Nanoparticles Encapsulated in FER Zeolite through a Layer Reassembling Strategy as Shape‐selective Hydrogenation Catalyst. Issue 10 (13th March 2018) - Zhao, Zhenchao; Li, Yanlu; Feyen, Mathias; McGuire, Robert; Müller, Ulrich; Zhang, Weiping
Abstract: Noble metal nanoparticles (NPs) encapsulated in zeolites bearing distinct shape‐selective properties at molecular level expand their new applications in catalysis. Here we report a synthesis strategy for the encapsulation of Pd NPs inside FER zeolite via a layer reassembling process. Pd precursors were introduced by swelling FER layers in RUB‐36 through the surfactant cetyltrimethylammonium cations (CTA + ) and then an ion‐exchange process at ambient temperature. Pd@FER was formed with a uniform diameter distribution of Pd NPs at about 1.4 nm during the topotactic transformation from layered zeolite precursors to 3‐dimensional zeolites followed by calcination. The as‐prepared Pd@FER catalyst exhibits distinct shape‐selective properties in hydrogenation reactions. It has relatively lower activity for 1‐hexene and almost no activity for 1‐phenyl‐1‐cyclohexene compared with Pd/RUB‐37 catalyst prepared via wet impregnation due to the restrictions of channels in the FER zeolite. On the contrary, Pd@FER shows very high hydrogenation activity for benzaldehyde and very low activity for diphenylmethanone hydrogenation, while Pd/RUB‐37 exhibits high hydrogenation activity for both benzaldehyde and diphenylmethanone. This synthesis strategy may be extended to other noble metals or two‐dimensional layered zeolite systems for size‐selective hydrogenation reactions. Abstract : There's the RUB : FER zeolite encapsulating Pd nanoparticles with excellent shape‐selective catalytic properties were constructed and synthesized through swelling RUB‐36, ion exchange, and topotactic conversion processes.